The British - Ebbutt, M.I. (Maud Isabel) 1867- (Avenel Books : Distributed by Crown Publishers, 1986)
Sixteen stories from the eight century onward representing Britain's myths and legends, with explanatory material. Includes Beowulf, Cuchulain, and Robin Hood.